Minahasa: the «success story» of Dutch colonialism in Indonesia - Schouten, Maria Johanna Christina (2019)
The Minahasans of northern Sulawesi underwent in the nineteenth century a rapid metamorphosis from a people that was considered as violent and savage into what seemed pious and orderly subjects of the Dutch colonal state. The texts proposes several motives for Minahasans’ conversion to Christianity and their enthusiasm for school education. Attention is also paid to the harsh economic exploitation under colonial rule, as well as to actions of resistance. A general outline of the colonial history of Indonesia provides the framework of the text.